TEA PLANTATION IN THE INDIAN SUB-CONTINENT DURING 19TH CENTURY: AN EXPLORATION OR EXPLOITATION - Noreen, Sumaira; Khan, Mahnoor (Journal of Arts & Social Sciences, 2024)
This article focusses on tea plantation efforts of British Government in different areas of the Indian subcontinent, including Assam, Darjeeling, Kumaoun, and Kangra Valley, since early 19th century onwards. The tea plantation drive took decades for the British government to succeed. The purpose of the study is to investigate the underlying socio-economic interests of the British government behind tea plantation in different areas of Indian sub-continent. The primary data evidence is collected from the official records at Punjab archives and other relevant online sources which are coupled with the secondary data sources. The data findings reveal that the British government’s ventures of tea plantation in different areas of Indian subcontinent had borne fruitful results for the government. But the tea plantation drive had caused an exploitation of the native people by making them serve the British government on their own lands and eventually losing their lands to the British government if they were unable to pay the tax levied upon them while using their own lands for the crop cultivation.